The House of Diligence in Rostov-on-Don - Petrusenko, Yuliya; Ivanova-Ilicheva, Anna (project baikal, 2021)
The aim of the study is to review the architectural-artistic, design and functional features of charity institutions through the example of the House of Diligence named after P. R. Maksimov, as well as peculiarities of the architect Nikolai Matveevich Sokolov’s creative method. The study was based on the historical analysis of P. R. Maksimov House of Diligence, archival and on-site investigations, and photofixation of the object. The article introduces new factual data and systematizes information on N. M. Sokolov’s creative legacy.
Keywords: architecture; charity institutions; architect N. M. Sokolov